TECHNOLOGIES OF DOMINATION AND THE SELF IN BRIEFING FOR A DESCENT INTO HELL BY DORIS LESSING - YILDIZ, VİLDAN (Fırat Üniveristesi, 2018)
Bu çalışma, Doris Lessing'in, Briefing for a Descent into Hell (1971) adlı eserinde, akıl ve akıl dışı ikili karşıtlığını yapı bozumuna uğratırken Foucaultcu baskı teknolojileri ve benlik teknolojilerine ulaştığını göstermeyi amaçlamaktadır. Romanda, Lessing akıl hastası kabul edilen Charles Watkins ana karakteri aracılığıyla, 1960'larda İngiltere'de yaşayan ayrıştırıcı uygulamalarla kuşatılmış modern insanı resmeder. Bireyi akıl/akıl dışı, medeni/ilkel ve normal/anormal gibi ikiliklerle kuran psikiyatri, arkeoloji ve eğitim gibi alanlar, Watkins ve diğer sözde deli karakterler üzerinden Lessing'in eleştiri oklarına maruz kalmıştır. Aşamalı yapılarla ayıran, sınıflandıran insan merkezci Batı epistemi, antik dönemin benlik teknolojilerinden—varoluş sanatından—uzaklaşmış ve yerleşmiş bilimsel bilginin yardımıyla bireyi öz-parçalanmışlığa itmiştir. Foucault baskı teknolojilerine karşı benlik teknolojilerinin bireyin kendini sosyal norm ve egemen yapılardan bağımsız olarak kurmasına olanak verdiğini kabul ederken, benzer şekilde, Lessing de akıldışını çıkış yolu olarak kullanan böyle bir özgürlük için yöntemler bulmaya çalışır. Bu yüzden, Lessing'in akıldışı savı Foucaultcu delilik ile kesişir ve benlik teknolojileri olarak Jungcu psikoloji ve Tasavvuf ile paralellik gösterir. Bu bağlamda, delilik kavramı çerçevesinde, bu çalışma Lessing'in Briefing for a Descent into Hell'inde özneyi kuran baskı teknolojileri ve benlik teknolojilerini irdeler.

This study aims to present that by deconstructing rational/irrational binary opposition in Briefing for a Descent into Hell (1971), Doris Lessing reaches out Foucauldian technologies of domination and technologies of the self that constitute the subject. In the novel, Lessing draws the picture of the modern man of 1960s in England, who is surrendered by the technologies of domination, by means of the protagonist Charles Watkins and accepted as mentally ill. Via Watkins and the other so-called insane characters, the areas such as psychiatry, archaeology and education which constitute the individual with the dualisms of rational/irrational, civilized/uncivilized and normal/abnormal are exposed to the arrows of criticism. The anthropocentric Western episteme that divides and classifies via hierarchal structures has gotten farther from the ancient culture's technologies of the self—the art of existence—and it has forced the individual to self-fragmentation with the help of the established scientific knowledge. While Foucault accepts that against the technologies of domination, the technologies of the self enable the individual constitute herself/himself free from social norms and dominant structures, similarly Lessing tries to find out the ways for that kind of freedom which uses the realm of the irrational as a way out. Therefore, Lessing's assertion of the irrational intercepts with the Foucauldian madness and parallels to Jungian psychology and Sufism as the technologies of the self. In this sense, basically within the concept of madness, this study examines the technologies of domination and the technologies of the self that construct the subject in Lessing's Briefing for a Descent into Hell.
Doris Lessing'in Briefing for a descent into hell adlı romanında baskı ve benlik teknolojileri
Keywords: İngiliz Dili ve Edebiyatı